Case report: mixed large-cell neuroendocrine and hepatocellular carcinoma of the liver - Gao, Xin; Wang, Heng; Niu, Zheyu; Liu, Meng; Kong, Xiaohan; Sun, Hongrui; Ma, Chaoqun; Zhu, Huaqiang; Lu, Jun; Zhou, Xu (Frontiers in Oncology, 2024)
Background：Cases of large-cell neuroendocrine carcinoma (NEC) concomitant hepatocellular carcinoma (HCC) are very rare. Based on the microscopic characteristics, mixed HCC-NEC tumors 2 can be divided into collision type and combined type. We report a patient with both collision and combined type HCC-NEC tumor at the same time. Case presentation：A 58-year-old man with hepatitis B and cirrhosis was found to have two masses in segment 5 and segment 8 of the liver, respectively. Preoperative imaging diagnosis was primary liver cancer. Indocyanine green retention test (ICG R15 ) <10% suggested that the patient can tolerate surgery. Partial hepatectomy was performed under the guidance of 3D reconstruction. Postoperative pathology showed that most of the tumors in S5 were large-cell neuroendocrine carcinoma (90%), and a small part were hepatocellular carcinoma (10%). The tumor in S8 of the liver was diagnosed as HCC combined with immunohistochemistry. After surgery, the patient underwent genetic testing, which indicated mutations in TP53 gene. The test of immune markers of the sample suggest that the patient may benefit little from immune checkpoint inhibitor therapy. The cisplatin and etoposide chemotherapy protocol to the patient following their surgery. Eight month later after the operation, Enhanced CT showed there was no recurrence or metastasis of the tumor. Conclusions：The case at hand augments the understanding of HCC-NEC mixed tumors, offering pivotal insights into their precise diagnosis and treatment modalities. Furthermore, we document a favorable prognosis, marked by an absence of recurrence signs thus far-a rarity in comparable instances. This enlightenment stands to facilitate the handling of ensuing cases and enhance patient prognoses.